294 Concurrent Classic Hodgkin Non-Hodgkin Lymphomas in a Post-Renal Transplant Setting. (11th January 2018) - Soliman, Mahmoud; Lee, John
Abstract: The development of classic Hodgkin lymphoma (cHL) synchronously or metachronously in chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) patients is quite rare and estimated to be less than 0.4%. We are presenting a rare case of synchronous Epstein-Barr virus (EBV)-positive cHL and atypical CLL/SLL in a post-renal transplant setting. A 76-year-old man with history of bladder cancer treated with cystoprostatectomy and chemotherapy and allograft transplant on tacrolimus presented with fatigue, fever, and mediastinal lymphadenopathy on CT scan. Lymph node biopsy showed architectural effacement by monomorphous population of small lymphocytes that are CD45+, pax5+, CD19+, CD20+/–, CD5+/–, CD10–, CD11c–, CD23–, CD25+, CD103–, Bcl6–, cyclin D1–, and dim kappa light chain restriction. Ki67 proliferation index was 10%-15%. This immunophenotype is indicative of a CD5 partially positive B-cell lymphoma with features of CLL, albeit CD23 negative. Singly scattered throughout the CLL were Hodgkin Reed-Sternberg (HRS) cells that were EBV+, CD30+, CD15+, MUM1+, pax5+, and CD20–. Bone marrow biopsy showed a granulomatous infiltrate with HRS cells occupying 30%-40% of the bone marrow cellularity and accompanied by increased reticulin fibrosis. Flow cytometry of the peripheral blood and bone marrow aspirate showed minimal involvement by CLL. The diagnosis was made of a composite EBV-positive cHL and CLL. The differential diagnosis includes a polymorphic post-transplant lymphoproliferative disorder with Hodgkin-like cells. This case of composite lymphoma is unique in that it is described in the post-transplant immunosuppression setting, which is most likely a contributing factor to the EBV-positive cHL, but not the CLL.